A Comparative Analysis of Seismological and Gravimetric Crustal Thicknesses below the Andean Region with Flat Subduction of the Nazca Plate. (20th August 2009) - Gimenez, Mario E.; Braitenberg, Carla; Martinez, M. Patricia; Introcaso, Antonio
Abstract : A gravimetric study was carried out in a region of the Central Andean Range between 28 ∘ and 32 ∘ south latitudes and from 72 ∘ and 66 ∘ west longitudes. The seismological and gravimetrical Moho models were compared in a sector which coincides with the seismological stations of the CHARGE project. The comparison reveals discrepancies between the gravity Moho depths and those obtained from seismological investigations (CHARGE project), the latter giving deeper values than those resulting from the gravimetric inversion. These discrepancies are attenuated when the positive gravimetric effect of the Nazca plate is considered. Nonetheless, a small residuum of about 5 km remains beneath the Cuyania terrane region, to the east of the main Andean chain. This residuum could be gravimetrically justified if the existence of a high density or eclogitized portion of the lower crust is considered. This result differed from the interpretations from Project "CHARGE" which revealed that the entire inferior crust extending from the Precordillera to the occidental "Sierras Pampeanas" could be "eclogitized". In this same sector, we calculated the effective elastic thickness (Te) of the crust. These results indicated an anomalous value of Te = 30 km below the Cuyania terrane. This is further conclusive evidence of the fact that the Cuyania terrane is allochthonous, for which also geological evidences exist.